Differences in Immune-Related Genes Underlie Temporal and Regional Pathological Progression in 3xTg-AD Mice - Fernandes, Adelaide (2022)
The prevalence of Alzheimer's disease (AD), the most common cause of age-associated dementia, is estimated to increase over the next decades. Evidence suggests neuro-immune signaling deregulation and risk genes beyond the amyloid-β (Aβ) deposition in AD pathology. We examined the temporal profile of inflammatory mediators and microglia deactivation/activation in the brain cortex and hippocampus of 3xTg-AD mice at 3- and 9-month-old. We found upregulated APP processing, decreased expression of CD11b, CX3CR1, MFG-E8, TNF-α, IL-1β, MHC-II and C/EBP-α and increased miR-146a in both brain regions in 3-month-old 3xTG-AD mice, suggestive of a restrictive regulation. Enhanced TNF-α, IL-1β, IL-6, iNOS, SOCS1 and Arginase 1 were only present in the hippocampus of 9-month-old animals, though elevation of HMGB1 and reduction of miR-146a and miR-124 were common features in the hippocampus and cortex regions. miR-155 increased early in the cortex and later in both regions, supporting its potential as a biomarker. Candidate downregulated target genes by cortical miR-155 included Foxo3, Runx2 and CEBPβ at 3 months and Foxo3, Runx2 and Socs1 at 9 months, which are implicated in cell survival, but also in Aβ pathology and microglia/astrocyte dysfunction. Data provide new insights across AD state trajectory, with divergent microglia phenotypes and inflammatory-associated features, and identify critical targets for drug discovery and combinatorial therapies.